Geographies of Ageing. Social Processes and the Spatial Uneveness of Population Ageing - Fenández Carro, Celia (Documents d’Anàlisi Geogràfica, 2012)
Amanda Davies, Amity James Geographies of Ageing. Social Processes and the Spatial Uneveness of Population Ageing Reino Unido / Estados Unidos Ashgate 2011 pp.209